King, Identity and Islamization: Psycho-social Aspects of Religious Conversion in Southeast Asia in the 15th â 17th Centuries - Hasbullah, Moeflich (TAWARIKH, 2009)
ABSTRACT: One of the most tremendous events in the history of Southeast Asia is the massive wave of Islamization, the process that still attracts big curiosity among the historians. Islamization has radically replaced the centuries-rooted pre-Islamic belief. Based on the fact that Islamization took place in the period of lively commerce of Southeast Asia, many have said that one of the strong motivations being Muslim was economic gains. Kingdoms and courts which mainly located in coastal ports whereby Islamization vigorously took place, gained much more state wealth from the 15-17th commercial activities. This paper examines this conclusion by looking at the phenomena deeper into indigenous worldview from the psycho-social perspective. Exploring Southeast Asian religious conversion from psycho-social perspective has come to the conclusion that indigenous converters did not merely see Islam as a religion, as a set of doctrinal worship. Global community, international cooperation and massive commercial activities conducted by Muslim traders have in fact served a value that converting to Islam meant changing identity to a brighter future.KEY WORDS: the massive wave of Islamization, kingdoms and courts, Southeast Asians, and psycho-social perspective.Â Â About the Author: Moeflich Hasbullah, M.A. is a Lecturer at the Department of Islamic History and Civilization, Faculty of Literature, Islamic State University (UIN) Sunan Gunung Djati in Bandung, West Java, Indonesia. He can be reached at: moeflich@gmail.com and moef_euy@yahoo.comHow to cite this article? Hasbullah, Moeflich. (2009). âKing, Identity and Islamization: Psycho-social Aspects of Religious Conversion in Southeast Asia in the 15th â 17th Centuriesâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.1-14. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 28, 2009); Revised (September 21, 2009); and Published (October 28, 2009).